Super‐Resolution Microscopy Using a Bioorthogonal‐Based Cholesterol Probe Provides Unprecedented Capabilities for Imaging Nanoscale Lipid Heterogeneity in Living Cells. Issue 9 (29th July 2021) - Lorizate, Maier; Terrones, Oihana; Nieto‐Garai, Jon Ander; Rojo‐Bartolomé, Iratxe; Ciceri, Dalila; Morana, Ornella; Olazar‐Intxausti, June; Arboleya, Aroa; Martin, Alexia; Szynkiewicz, Marta; Calleja‐Felipe, Maria; Bernardino de la Serna, Jorge; et al.
Abstract: Despite more than 20 years of work since the lipid raft concept was proposed, the existence of these nanostructures remains highly controversial due to the lack of noninvasive methods to investigate their native nanorganization in living unperturbed cells. There is an unmet need for probes for direct imaging of nanoscale membrane dynamics with high spatial and temporal resolution in living cells. In this paper, a bioorthogonal‐based cholesterol probe (chol‐N3 ) is developed that, combined with nanoscopy, becomes a new powerful method for direct visualization and characterization of lipid raft at unprecedented resolution in living cells. The chol‐N3 probe mimics cholesterol in synthetic and cellular membranes without perturbation. When combined with live‐cell super‐resolution microscopy, chol‐N3 demonstrates the existence of cholesterol‐rich nanodomains of <50 nm at the plasma membrane of resting living cells. Using this tool, the lipid membrane structure of such subdiffraction limit domains is identified, and the nanoscale spatiotemporal organization of cholesterol in the plasma membrane of living cells reveals multiple cholesterol diffusion modes at different spatial localizations. Finally, imaging across thick organ samples outlines the potential of this new method to address essential biological questions that were previously beyond reach. Abstract : Direct imaging and characterization of nanoscale lipid heterogeneity in living cells with high temporal and spatial resolution using developed bioorthogonal cholesterol probe and nanoscopy are introduced. This probe enables tackling biological questions that were previously beyond reach. Visualization of cholesterol distribution through thick tissues outlines the tool's potential to investigate the role of cholesterol in health and disease.